External respiration function in adolescents with childhood cerebral palsy who do and do not participate in sports - Rubtsova, N.O.; Artamonova, T.V.; Spirina, I.K. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the features of the manifestation of the function of external respiration in adolescents with cerebral palsy, engaged and not engaged in sports. Methods and structure of the study. 24 adolescents with cerebral palsy (diagnosis: spastic diplegia, preserved intellect) participated in the scientific study. The group of athletes consisted of 12 sledge hockey players from the Krylia Sovetov and Spartak teams (Moscow) aged 12-14, and the group of non-athletes consisted of 12 students from Boarding School No. 17 (Moscow) aged 12-14. The study was conducted in April and May 2025. To assess the level of external respiration function in adolescents with cerebral palsy who do and do not participate in sports, the following indicators were studied: vital capacity (VC), peak expiratory flow rate (PEFR), respiratory rate per minute (RR), Stange test, and Genchi test. Results and conclusions. A comparison of respiratory function indicators of adolescents with cerebral palsy who are engaged and not engaged in sports allowed us to assess their current parameters of pulmonary function, to substantiate the importance of new data in terms of increasing the rehabilitation potential of adolescents with cerebral palsy through systematic and targeted sports training. The experimental data obtained open up a new perspective on the resource possibilities of regular and purposeful adaptive sports activities in terms of increasing the level of functional capabilities of adolescents with cerebral palsy and confirm the need to include specially developed blocks of breathing exercises in the methodology of comprehensive rehabilitation of children with musculoskeletal system disorders.